History on trial my day in court with a Holocaust Denier - Lipstadt, Deborah E. 1947- (Ecco, 2005)
A chronicle of the author's five-year legal battle with writer David Irving, a prolific supporter of Holocaust denial, describes how the author and a team of experts defended against Irving's libel suit while exposing his distortions of history.